THEORETICAL MODEL EVALUATION OF STOCK PRICE AND EXCHANGE RATE RELATIONSHIPS IN BRICS COUNTRIES - Sianipar, Makmur; Indrayono, Yohanes; Sasongko, Hendro (Yayasan Education and Social Center, 2025)
This study investigates the theoretical and empirical relationships between stock prices and exchange rates within the BRICS countries (Brazil, Russia, India, China, South Africa, and Indonesia), particularly focusing on Indonesia following its official inclusion in BRICS on January 6, 2025. Using a daily time series dataset from June 2023 to May 2025, this research applies the Granger Causality Test to evaluate the direction of causality between capital and foreign exchange markets. The study is grounded in four major theoretical frameworks: flow-oriented, stock-oriented, portfolio balance, and asset market models. The analysis reveals a heterogeneous structure of interdependence across BRICS countries, encompassing both unidirectional and bidirectional causalities. Notably, Indonesia’s capital market (JSX) demonstrates predictive influence over the domestic exchange rate (IDR), supporting the stock-oriented hypothesis. Moreover, the South African Rand (ZAR) exhibits dominant influence across multiple BRICS markets, while China’s Yuan (CNY) significantly affects the South African stock index, confirming China’s pivotal economic role. The study also identifies feedback loops between several country pairs, indicating strong financial integration and information transmission. This research contributes to the literature by incorporating daily data analysis and exploring the impact of Indonesia’s BRICS membership, an area previously underexplored. It offers theoretical enrichment by mapping empirical findings onto established models and provides policy insights for enhancing macro-financial coordination and volatility risk management among BRICS nations.